Extraction of Gelatin From Poultry Byproduct: Influence of Drying Method on Structural, Thermal, Functional, and Rheological Characteristics of the Dried Gelatin Powder - Rather, Jahangir A.; Majid, Syed Darakshan; Dar, Aamir Hussain; Amin, Tawheed; Makroo, H. A.; Mir, Shabir Ahmad; Barba, Francisco J.; Dar, B. N. (Frontiers in Nutrition, 2022)
The poultry processing industrial wastes are rich sources of gelatin protein, which can be utilized for various industrial sectors. The present investigation was conducted to evaluate the effect of freeze-drying (FD) and hot air drying (HAD) on the physicochemical, structural, thermal, and functional characteristics of chicken feet gelatin. The yield (%) of extracted FD and HAD gelatin was 14.7 and 14.5%, respectively. The gelatin samples showed lower percent transmittance in the UV region. The FTIR bands were at 3,410–3,448 cm−1, 1,635 cm−1, 1,527–334 cm−1, and 1,242–871 cm−1 representing amide-A, amide-I, amide-II, and amide-III bands, respectively. The water activity of HAD was higher (0.43) than in FD (0.21) samples and pH were 5.23 and 5.14 for HAD and FD samples, respectively. The flow index (n) of 6.67% gelatin solutions was 0.104 and 0.418 with consistency coefficient (k) of 37.94 and 31.68 for HAD and FD samples, respectively. The HAD sample shows higher gel strength (276 g) than the FD samples (251 g). The foaming capacity (FC) and foaming stability (FS) of FD samples were 81 and 79.44% compared to 62 and 71.28% for HAD, respectively. The emulsion capacity and emulsion stability of HAD gelatin were higher at 53.47 and 52.66% than FD gelatin. The water holding capacity (WHC) and oil binding capacity (OBC) of FD were lower, that is, 14.3 and 5.34 mL/g compared to HAD gelatin having 14.54 and 6.2 mL/g WHC and OBC, respectively. Hence, the present study indicated that gelatin samples can be utilized in various food products for enhancing functionality and can be used for developing edible packaging materials.